International Railway Economics / Studies in Management and Efficiency - Button K.J; Pitfield D.E (Gower Publishing, 1985)
The theme of this book is the need to improve efficiency within railway operations and the contributors offer constructive suggestions based upon detailed assessment of specific problems. Preface, Introduction, Management and Performance Indicators, A Survey of Recent Developments in the Measurement of Rail Total Factor Productivity, Revitalization of the US Rail Freight Industry: An Organizational Perspective, The Development of Management Information to Meet the Needs of a New Management Structure for British Rail, Costing, Rail Cost Analysis, The Consistent Treatment of Rail and Road Freight Costs in Australia, Forecasting and Evaluation and Investment, The Determinants of Fixed-Rail Transit Demand - An International Cross-Sectional Comparison, An Evaluation of the Tyne side Metro, Forecasting Rail Freight Flows in Britain, Efficiency, European Railway Comparisons - What Can we Learn?, Railways in Rural Areas, Efficiency of Railway Transportation: The Indian Experience, Name and Subject Index.